A ANALISIS KEPUASAN PASIEN TERHADAP PELAYANAN RAWAT JALAN BERDASARKAN PERSEPSI DAN HARAPAN PASIEN DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Laksono, Adi; Kirnanda, Putri Listiya (Journal of Hospital Administration and Management (JHAM), 2026)
An outpatient satisfaction RSM Ahmad Dahlan survey conducted in the 2022-2024 period showed a decrease in patient satisfaction levels, from 98,67% to 98,27%.. This study aims to analyze patient satisfaction with outpatient services based on patient perceptions and expectations at RSM Ahmad Dahlan Kediri City using the Importance Performance Analysis (IPA) method. This study used a quantitative descriptive design with a cross-sectional approach. The study employed a quantitative descriptive design with a cross-sectional methodology. An unintentional sampling strategy was used to pick 100 outpatient respondents for the study. Data were collected using a questionnaire that covered five elements of service quality: reliability, assurance, responsiveness, empathy, and concrete evidence. The Wilcoxon signed rank test and Importance Performance Analysis (IPA) matrix were used to analyse the data. The results showed an overall patient satisfaction level of 95.65%. The tangible dimension recorded the highest satisfaction level (98.40%), while the reliability dimension showed the lowest satisfaction level (91.90%). Statistical analysis revealed a significant difference in patient perceptions and expectations (p < 0.05). The Importance Performance Analysis (IPA) matrix identifies various service areas that require immediate improvement in the dependability and responsiveness dimensions. Regular evaluation and service improvement strategies are needed to increase and maintain outpatient satisfaction especially in term of service time and empathy in handling complaints. Keywords : Patient Satisfaction, Outpatient Services, Perceptions and Expectations, Importance Performance Analysis